The COVID-19 pandemic: Clinical practice advice for gastroenterologists, hepatologists, and liver transplant specialists - Kabaçam, Gökhan; Dayangaç, Murat; Üçbilek, Enver; Erçin, Cemal Nuri; Günsar, Fulya; Akyıldız, Murat; Akarsu, Mesut; Demir, Mehmet; Kaymakoğlu, Sabahattin; Karasu, Zeki; İdilman, Ramazan (Turkish Journal of Gastroenterology, 2020)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is a novel acute infectious disease that has rapidly reached staggering pandemic proportions. This document addresses gastroenterologists, hepatologists, liver transplant specialist and health-care professionals working in the field of liver diseases and liver transplantation. It has been composed based on a limited number of publications, recommendations of national and international liver and organ transplantation societies, and COVID-19 patient experiences around the world. The purpose of this document is to provide information addressing questions and concerns about COVID-19, to reveal the effects of the novel disease on patients with chronic liver disease and liver transplant recipients, and to share information about the ways in which this pandemic will affect clinical practices. We, the Turkish Association for the Study of the Liver (TASL), would like to remind you that this text could actually be not a practical guide. It is imperative to act according to the standards set by health-care institutions and the Ministry of Health, Republic of Turkey.